PENGARUH KOMPETENSI MAHASISWA TERHADAP PEMILIHAN KONSENTRASI DI PRODI ILMU KOMUNIKASI FIS UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Efrilian Dewa; Solihah Titin Sumanti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to analyze the effect of the competence of communication science students on their choice of concentration in the physical communication science study program at the State Islamic University of North Sumatra. The research method used in this study is a descriptive and associative research method with a survey approach. This study uses a questionnaire as a tool to collect primary data. The population as well as the sample in this study were students of the Communication Studies Program at the State Islamic University of North Sumatra. The statistical analysis used in this research is multiple linear regression analysis using SPSS version 20. The results of this study indicate that the competency variables simultaneously (together) and partially (alone) have no positive and significant effect on the decision to choose a concentration in the Communication Studies Study Program. This is evidenced by the results of the T test with a significance level above 0.05 and the results of the F test with a significance level above 0.05, as well as the results of the coefficient of determination test, which shows that the influence of competence on the decision to choose a concentration in the Communication Sciences Study Program at the State University of North Sumatra is only 64% and the rest is influenced by other variables at 46%. That means that the hypothesis in this study was rejected.